Analysis of Ultimate Bearing Capacity of Bore Pile Foundation in High-Rise Building at Pulomas, East Jakarta - Wisan, Nathanael Edward; Bali, Ika; Sudjatmiko, Eddy Triyanto (President University, 2023)
Soil condition at the Pulomas tower project site with a water level of 17 m below the ground and the hard soil at ground depth of 18 – 22 m, as well as the project location surrounded by houses and office buildings made the choice of bore pile as the foundation in this project. This condition is the background to the need for a bore pile capacity analysis in this tower project. The objective of this study is to analyze the bore pile capacity which is based on Standard Penetration Test (SPT) and Cone Penetration Test (CPT) and to be compared to the interpretation result of static loading test at a tower project location in East Jakarta. The ultimate bearing capacity of bore pile foundation was calculated using Meyerhof method and Reese & Wright method, and static loading test using Chin method. This study indicated that the ultimate bearing capacity using Reese & Wright method is closer to the interpretation result of static loading test from Chin method compared to Meyerhof method.